Palladium incorporated on carbonaceous catalyst for Suzuki coupling reaction in water - Rathod, P. V.; Jadhav, V.H. (Tetrahedron Letters, 2017)
A new palladium incorporated carbonaceous catalyst Pd@CC SO3H -NH2 was synthesized by introducing palladium on glucose derived carbocatalyst. The catalyst was well characterized and was used for the Suzuki coupling of phenyl boronic acid with different aryl halides under aqueous conditions. This green methodology represents a ligand free, cost-effective and operationally convenient method for the synthesis of a variety of biaryl's under the conditions that are tolerant for a broad range of functional groups with good to excellent yields. Moreover, the catalyst could be easily recycled and reused at least five times without any significant loss of its catalytic activity.